Is Caloric Efficiency an Accurate Method to Estimate Soybean Meal Net Energy in Nursery Pigs? - Ty H. Kim; Pau Salgado-Lopez; Jessica L. Smallfield; Mike D. Tokach; Joel M. DeRouchey; Jason C. Woodworth; Robert D. Goodband; Katelyn N. Gaffield; Jordan T. Gebhardt; Henrique S. Cemin; Ernie Hansen; Morgan D. Hart; et al. (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 4,730 pigs (PIC 337 × L 42) were used in a 20-d study to determine if the caloric efficiency (CE) method is an accurate predictor of soybean meal (SBM) NE in nursery pigs. Pigs were blocked by sow source, entry date, and initial BW (initially 26.5 ± 0.87 lb) and allotted to one of 12 dietary treatments in a randomized complete block design. The twelve treatments were arranged in a 3 × 4 factorial with main effects of SBM NE relative to corn used in diet formulation (80, 100, or 120%) and SBM level (26, 30, 34, or 38%). The same diet was used for each treatment containing 26% SBM, and this served as the base within each SBM NE level. There were 30 to 35 pigs per pen. There were 32 replications of the base treatment and 12 replications of the remaining nine treatments across two rooms. Pens of pigs were weighed, and feed disappearance was measured at the beginning and at the end of the study to determine ADG, ADFI, F/G, and CE. On d 21, following the completion of the growth study, a blood sample was collected from five pigs (two barrows and three gilts) per pen (84 pens; 420 pigs total) to determine serum urea nitrogen. Pigs were fasted for approximately 12 h prior to sample collection. To test SBM level × SBM NE in formulation interactions, the 30, 34, and 38% SBM level treatments were used. No SBM level × SBM NE in formulation interactions were observed. A tendency for a quadratic effect of SBM level was observed (P < 0.10) for ADG, where ADG tended to increase as SBM level increased from 26 to 34% but decreased as SBM level further increased to 38%. A quadratic effect of SBM level was observed (P < 0.05) for ADFI, where ADFI remained constant as SBM levels increased from 26 to 34% but decreased as SBM level increased to 38%. Thus, F/G improved linearly (P < 0.05) as the SBM level increased. To test simple effects of SBM level within SBM NE in formulation, all four SBM level treatments were used. A quadratic effect of SBM level within the 80% SBM NE in formulation was observed (P < 0.05) for ADG and ADFI, where ADG and ADFI increased as SBM level increased from 26 to 34% but decreased as SBM level increased to 38%. A linear effect of SBM level was observed (P < 0.05) for F/G within all three formulation strategies, where F/G improved as SBM level increased within each formulation strategy. Caloric efficiency improved (linear, P < 0.001) with increasing SBM level within each of the formulation strategies. The improvement in F/G appears to be a response to the SBM level rather than SBM NE itself. Thus, the CE method may not be an accurate method of predicting SBM NE in nursery pigs.
Keywords: caloric efficiency; net energy; nursery pigs; soybean meal